Self-Concept and Career Maturity in Generation Z in Palembang City: Konsep Diri dan Kematangan Karier pada Generasi Z di Kota Palembang - Wita Farla; Nia Meitisari; Lina Dameria Siregar (Universitas Muhammadiyah Sidoarjo, 2025)
This research is motivated by the importance of Generation Z having career maturity because it will be related to career decision-making. Generation Z needs to explore themselves to support future career development. The purpose of this study was to empirically analyze the effect of self-concept on the career maturity of Generation Z in Palembang City and to find out the differences in self-concept and career maturity of Generation Z in Palembang City based on gender. The population was Generation Z in Palembang City, which amounted to 138.444 people. The number of samples taken was 100 respondents sing accidental sampling. The data were taken by distributing questionnaires to respondents. The data was processed and analyzed using simple linear regression analysis techniques and the Independent Sample t-test. This study’s results demonstrated that self-concept significantly affected career maturity, and based on gender, there is no significant difference between the self-concept and career maturity of Generation Z in Palembang. Based on the results of this study, Generation Z, both men and women, can improve their ability to assess themselves so that they are able to recognize and evaluate the potentials that exist in themselves. This research can also help organizations in formulating career development policies for Generation Z.